How I met your mother. Season seven [videorecording (DVD)]. - Hannigan, Alyson, 1974-; Harris, Neil Patrick, 1973-; Segel, Jason, 1980-; Radnor, Josh, 1974-; Smulders, Cobie, 1982- (20th Century Fox, 2012)
With both a baby and a wedding on the way, change is in the air and awesomeness abounds. As Marshall and Lily move away to start their family, Ted continues the search for the woman of his dreams. Meanwhile, Robin reveals a shocking secret and Katie Holmes joins the fun in the long-awaited return of the Slutty Pumpkin.